Reverse Chemical Ecology Suggests Putative Primate Pheromones. (22nd November 2021) - Zaremska, Valeriia; Fischer, Isabella Maria; Renzone, Giovanni; Arena, Simona; Scaloni, Andrea; Knoll, Wolfgang; Pelosi, Paolo
Abstract: Pheromonal communication is widespread among living organisms, but in apes and particularly in humans there is currently no strong evidence for such phenomenon. Among primates, lemurs use pheromones to communicate within members of the same species, whereas in some monkeys such capabilities seem to be lost. Chemical communication in humans appears to be impaired by the lack or malfunctioning of biochemical tools and anatomical structures mediating detection of pheromones. Here, we report on a pheromone-carrier protein (SAL) adopting a "reverse chemical ecology" approach to get insights on the structures of potential pheromones in a representative species of lemurs ( Microcebus murinus ) known to use pheromones, Old-World monkeys ( Cercocebus atys ) for which chemical communication has been observed, and humans ( Homo sapiens ), where pheromones and chemical communication are still questioned. We have expressed the SAL orthologous proteins of these primate species, after reconstructing the gene encoding the human SAL, which is disrupted due to a single base mutation preventing its translation into RNA. Ligand-binding experiments with the recombinant SALs revealed macrocyclic ketones and lactones as the best ligands for all three proteins, suggesting cyclopentadecanone, pentadecanolide, and closely related compounds as the best candidates for potential pheromones. Such hypothesis agrees with the presence of a chemical very similar to hexadecanolide in the gland secretions of Mandrillus sphinx, a species closely related to C. atys . Our results indicate that the function of this carrier protein has not changed much during evolution from lemurs to humans, although its physiological role has been certainly impaired in humans.